PENGARUH GREEN MARKETING DAN BRAND IMAGE TERHADAP MINAT BELI AMDK MEREK AQUA DI KALANGAN MAHASISWA S1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - Bq. Khaerunnisa (Distribusi - Journal of Management and Business, 2019)
This study aims to determine the effect of geen marketing and brand image on buying interest of mineral water brand of Aqua among undergraduate degree students of the Faculty of Economics and Business, University of Mataram. This study uses two independent variables; Green Marketing, namely products, prices, promotions and places, and Brand Image, namely professional impression, modern impression, serving all segments and attention to consumers. The sample in the study were 100 respondents using accidental sampling. The method of data analysis uses quantitative methods and analyzed using multiple linear regression analysis. The results of this study are Green Marketing has a positive effect on buying interest. while Brand Image has a negative effect on buying interest.